An empirical analysis of factors that determine poverty among the beneficiaries of Pakistan Poverty Alleviation Fund - Owolabi Yusuf, Muhammad-Bashir; Shirazi, Nasim Shah; Mat Ghani, Gairuzazmi (Emerald Group Publishing, 2016)
Purpose – This study aims to examine the determinants of poverty among microcredit beneficiaries in Pakistan Poverty Alleviation Fund.Design/methodology/approach – The study is based on a nationwide survey of microcredit beneficiaries of Pakistan Poverty Alleviation Fund. Using the national poverty line, this study classified borrowers into the poor and the non-poor. A Tobit model was estimated to examine the determinants of poverty among the borrowers. Findings – The model was found to fit the data well and six out of the ten specified independent variables are found to be statistically significant. Practical implications – The results of the study can be helpful in fully characterizing poverty dynamics and in policy formulation in using microcredit to reduce poverty. Originality/value – The paper is the first to examine the determinants of poverty among Pakistan Poverty Alleviation Fund recipients